Dinamika Komunikasi Interpersonal Customer Service dan Kepala Sekolah Dalam Proses Layanan SIPLAH di Bank Sumsel Babel Syariah - Khalisya Rahma (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to explore the dynamics of interpersonal communication between the customer service officers of Bank Sumsel Babel Syariah and school principals in the SIPLah service process. The research focuses on how both parties build interaction, convey information, and manage obstacles that arise during the service process. A qualitative approach was used through interviews and observations to gain insight into the participants’ experiences. The findings reveal that the effectiveness of interpersonal communication is influenced by the clarity of information, the level of empathy, and the responsiveness demonstrated by customer service officers. Meanwhile, school principals contribute by providing accurate data and showing readiness to follow the required procedures. Additionally, challenges such as differences in understanding SIPLah’s technical aspects and limited time often affect the fluency of the service process. This study concludes that effective interpersonal communication plays a crucial role in streamlining the service and fostering a more harmonious working relationship between schools and the bank